FUNGSI EKSPRESIF BERBAHASA JAWA PADA NOVEL SEKAR RATRI KARYA RITA NUGROHO DWI KRISNAWATI: KAJIAN PRAGMATIK - Rosiana Rachim; Eka Yuli Astuti; Ucik Fuadhiyah (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
The purpose of this research is to describe the types of expressive speech acts in Javanese language in novels and expressive speech acts on politeness and impoliteness in Javanese language in novels. The method of this research is descriptive qualitative approach with results and discussion in the form of narration. The data collection method is by listening method and the data collection technique is note taking. The data in this research is the speech of the characters in the novel Sekar Ratri which contains expressive speech acts. The formulation of the problem in this research is the type of expressive speech acts in Javanese language in Sekar Ratri novel and expressive speech acts on politeness and impoliteness in Javanese language. The results of this study there are three classifications in the research, namely expressive speech acts in Javanese, expressive speech acts in Javanese against politeness, and expressive speech acts in Javanese against impoliteness. Javanese expressive speech acts in Sekar Ratri novel have eight types of expressive speech acts, namely happy, sad, thank you, grateful, praise, patience, annoyance, and sarcasm. The expressive speech acts are combined with politeness and impoliteness in Javanese language.